1999
DOI: 10.1300/j137v02n01_10
|View full text |Cite
|
Sign up to set email alerts
|

Homeless and Indigenous in Minneapolis

Abstract: Indigenous peoples are overrepresented in the homeless population. This paper examines the extent to which homelessness and some of its possible antecedents and consequences differ for indigenous peoples and majority whites residing in the city of Minneapolis. We conclude that being homeless and indigenous in Minneapolis is a significantly different experience for this group than it is for majority whites. The cultural context of indigenous homelessness reflects higher poverty and inconsistent patterns of empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
(12 reference statements)
2
9
0
Order By: Relevance
“…Importantly, our results suggest that reservation and reserve cultures quietly absorbs most homeless episodes, particularly those that occur on the reservation through making room for relatives and friends regardless of overcrowding (see also Owen et al 2007). Our results are congruent with other studies that have shown that those who have ever been homeless manifest more physical health, mental health, and substance abuse problems suggesting that experiences of homelessness are related to more tenuous adjustment and that the experiences may be persistent (Kahn et al 1992;Kasprow and Rosenheck 1998;Owen et al 2007;Westerfelt and Yellow Bird 1999). With the current data, it is impossible to discern the effects of parent/caretaker histories of homeless on the parenting of the study children.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Importantly, our results suggest that reservation and reserve cultures quietly absorbs most homeless episodes, particularly those that occur on the reservation through making room for relatives and friends regardless of overcrowding (see also Owen et al 2007). Our results are congruent with other studies that have shown that those who have ever been homeless manifest more physical health, mental health, and substance abuse problems suggesting that experiences of homelessness are related to more tenuous adjustment and that the experiences may be persistent (Kahn et al 1992;Kasprow and Rosenheck 1998;Owen et al 2007;Westerfelt and Yellow Bird 1999). With the current data, it is impossible to discern the effects of parent/caretaker histories of homeless on the parenting of the study children.…”
Section: Resultssupporting
confidence: 87%
“…In the Wilder study, the level of selfreported mental health problems of those who had experienced actual episodes of homelessness (56%) was very similar to that of the near-homeless (51%), but those who had been actually homeless reported higher levels of reported traumatic brain injury (40% vs. 29%) (Owen et al 2007). Westerfelt and Yellow Bird (1999) reported a much lower rate of psychiatric hospitalization among Indigenous homeless people (6.7%) compared to their non-Indigenous counterparts (24.3%).…”
Section: Characteristics Of Indigenous People Who Have Experienced Epmentioning
confidence: 91%
See 1 more Smart Citation
“…In particular, studies have indicated that homeless AI/ANs have much higher rates of alcohol consumption and alcohol-related problems than the general population (Kasprow & Rosenheck, 1998;Kramer & Barker, 1996;Lobo & Vaughan, 2003). Although research is mixed concerning whether homeless AI/ANs consume alcohol at greater quantities or frequencies than other homeless individuals, their experience of alcohol problems is generally more severe compared to homeless non-AI/ANs (Gamst et al, 2006;Kahn et al, 1992;Kasprow & Rosenheck, 1998;Travis, 1991;Westerfelt & Yellow Bird, 1999).…”
Section: Homelessness Alcohol Use and Alcohol-related Problems Amonmentioning
confidence: 99%
“…Compared to their counterparts on reservations, urban AI/ANs have less familial and other social support, fewer opportunities to engage in traditional cultural and spiritual practices, and less access to culturally appropriate health care services (Castor et al, 2006;Evans-Campbell, Lindhorst, Huang, & Walters, 2006;Jackson, 2002;Lobo, 2001). Perhaps as a result of these factors, urban AI/ANs experience a greater prevalence of homelessness than do non-AI/ANs living in cities (Westerfelt & Yellow Bird, 1999;Whitbeck et al, 2011). Considering their population share, the prevalence of homelessness among AI/ANs in major U.S. cities is disproportionately high.…”
Section: The Urban Ai/an Experience Of Alcohol-related Problems and Hmentioning
confidence: 99%